A Retrospective Study on Applications of the Lindley Distribution (Journal of Nonlinear Modeling and Analysis, 2024)
The need for efficient statistical models has increased with theflow of new data, which makes distribution theory a particularly interestingand attractive field. Here, we provide a thorough study of the applicationsof the Lindley distribution and its diverse generalizations. More precisely, wereview some special applications in various areas, such as time series analysis,stress strength analysis, acceptance sampling plans and data analysis. We alsoconduct a comparative study between the Lindley distribution and some of itsgeneralizations by using four real-life data sets.